Prognostic factors for persistent symptoms in adults with mild traumatic brain injury: an overview of systematic reviews - Julien Déry; Béatrice Ouellet; Élaine de Guise; Ève-Line Bussières; Marie-Eve Lamontagne (Systematic Reviews, 2023)
Abstract Background Mild traumatic brain injury (mTBI) is an increasing public health problem, because of its persistent symptoms and several functional consequences. Understanding the prognosis of a condition is an important component of clinical decision-making and can help to guide the prevention of persistent symptoms following mTBI. The prognosis of mTBI has stimulated several empirical primary research papers and many systematic reviews leading to the identification of a wide range of factors. We aim to synthesize these factors to get a better understanding of their breadth and scope. Methods We conducted an overview of systematic reviews. We searched in databases systematic reviews synthesizing evidence about the prognosis of persistent symptoms after mTBI in the adult population. Two reviewers independently screened all references and selected eligible reviews based on eligibility criteria. They extracted relevant information using an extraction grid. They also rated independently the risk of bias using the ROBIS tool. We synthesized evidence into a comprehensive conceptual map to facilitate the understanding of prognostic factors that have an impact on persistent post-concussion symptoms. Results From the 3857 references retrieved in a database search, we included 25 systematic reviews integrating the results of 312 primary articles published between 1957 and 2019. We examined 35 prognostic factors from the systematics reviews. No single prognostic factor demonstrated convincing and conclusive results. However, age, sex, and multiple concussions showed an affirmatory association with persistent post-concussion outcomes in systematic reviews. Conclusion We highlighted the need for a comprehensive picture of prognostic factors related to persistent post-concussion symptoms. We believe that these prognostic factors would guide clinical decisions and research related to prevention and intervention regarding persistent post-concussion symptoms. Systematic review registration PROSPERO CRD42020176676